ChemInform Abstract: Efficient Synthesis of Functionalized 6‐Arylsalicylates via Microwave‐Promoted Suzuki Cross‐Coupling Reaction. Issue 8 (25th February 2014) - Liu, Yu‐Chao; Huang, Zhi‐You; Chen, Qiong; Yang, Guang‐Fu
Abstract The two‐step procedure gives access to the title compounds starting from iodo salicylate (I) and a broad variety of arylboronic acids within a very short time and good to excellent yields.